Raman active phonon modes of cubic In2O3. Issue 6 (15th January 2014) - Kranert, Christian; Schmidt‐Grund, Rüdiger; Grundmann, Marius
Abstract <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> We introduce a symmetry assignment for the Raman active phonon modes for the cubic modification of indium sesqui‐oxide In2O3. Using a resonant excitation at <alternatives> <![CDATA[$\lambda _{\rm exc} = 325\;{\rm nm}, $]]> <inline-graphic xlink:href="ark:/27927/pghmhqkcr6" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> we observed 19 out of 22 expected first‐order Raman modes, of which many have not been reported before. This knowledge on the Raman spectrum is crucial for the interpretation of obtained Raman spectra, both resonantly and non‐resonantly ex‐ cited, and for the material characterization based on it. The phonon mode symmetry was determined based on polarized measurements on two In2O3 thin films with (001) and (111) orientation. The measurements were carried out at T = 10 K to minimize the linewidth for the separation of spectrally close lines. Besides the energy of the different phonon modes, we give their linewidths and relative intensities. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)